Financial network systemic risk contributions - Nikolaus Hautsch; Julia Schaumburg; Melanie Schienle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
We propose the realized systemic risk beta as a measure for financial companies' contribution to systemic risk given network interdependence between firms' tail risk exposures. Conditional on statistically pre-identified network spillover effects and market and balance sheet information, we define the realized systemic risk beta as the total time-varying marginal effect of a firm's Value-at-risk (VaR) on the system's VaR. Suitable statistical inference reveals a multitude of relevant risk spillover channels and determines companies' systemic importance in the U.S. financial system. Our approach can be used to monitor companies' systemic importance allowing for a transparent macroprudential regulation.
Keywords: G01; G18; G32; G38; C21; C51; C63; 330; Systemic risk contribution; systemic risk network; Value at Risk; network topology; two-step quantile regression; time-varying parameters; Bank; Finanzsektor; Unternehmensnetzwerk; Systemrisiko; Risikomaß; USA